Decentralized adaptive control of uncertain interconnected systems with triggering state signals - Zhang, Zhirong (2022)
Backstepping is a powerful technique of control design for uncertain systems and has been well received. As it involves differentiating virtual control signals recursively, the involved signals must be differentiable. However, when the measured states are only transmitted based on event-triggered conditions, such requirement will not be met, making the recursive backstepping design procedure inapplicable. Thus it is still an open problem to study how an event-triggered scheme is employed to transmit state signals in decentralized control of uncertain interconnected systems with dynamic interactions. In this paper, we present a solution by constructing a new decentralized adaptive backstepping-based control algorithm capable of coping with discontinuity caused by state-triggering. With aid of appropriately chosen Lyapunov functions, all signals in the closed-loop system are ensured globally uniformly bounded. Simulation results are presented to demonstrate the effectiveness of the proposed methodology.